Variable Pay, Industrial Relations and Foreign Ownership: Evidence from Germany - Uwe Jirjahn; John S. Heywood (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
We use a representative sample of German establishments to show that those with foreign ownership are more likely to use performance appraisal, profit sharing and employee share ownership than are those with domestic ownership. Moreover, we show that works councils are associated with an increased probability of using each of the three practices when under domestic ownership but not when under foreign ownership. These results inform the on-going debate over institutional duality, the extent to which foreign firms adopt uniform practices independent of local institutions and the extent to which they adapt and participate in those local institutions.
Keywords: M52; J50; F23; 330